Implementation of Humanistic Education in Shaping to a Moderate Attitude in Elementary Schools - Musthofa, Musthofa; Nasikhin; Ahmad Zahiruddin Mohd Zabidi (Edukasia Islamika : Jurnal Pendidikan Islam, 2023)
This study analyzes the implementation of humanistic education in shaping a moderate attitude  among elementary school students within the broader context of promoting religious  moderation and critical citizenship. The research aims to explore how humanistic education  contributes to fostering critical thinking, collaboration, innovation, and democratic values at the elementary level. Employing a qualitative method, data were collected through in-depth  interviews, observations, documentation studies, and surveys involving 54 students, four  teachers, and three parents from two elementary schools in the Batang Regency. Thematic  analysis was utilized to identify patterns across the collected data. The findings demonstrate  that humanistic education strengthens students' intellectual capacities through 4C-based  learning (Creativity and Innovation, Collaboration, Communication, Critical Thinking, and  Problem-Solving) and enhances humanitarian and democratic narratives embedded within  character education programs. Survey results revealed high percentages of nationalist attitudes  (93.3%), tolerance (90.6%), non-violent tendencies (93.3%), and cultural adaptability  (89.75%) among students. The study concludes that integrating humanistic education with  religious moderation efforts significantly shapes moderate attitudes in young learners. These  findings imply that educational institutions should systematically adopt humanistic approaches  to cultivate moderate, tolerant, and critically engaged citizens from an early stage.